2019
DOI: 10.4103/ijo.ijo_326_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of retropupillary iris claw versus scleral-fixated intraocular lens in the management of post-cataract aphakia

Abstract: Purpose:To compare the visual outcomes and complications between the eyes receiving retropupillary iris claw intraocular lens (IOL) and scleral-fixated IOL (SFIOL) for post-cataract aphakia.Methods:Medical records of consecutive patients who had iris claw IOL and SFIOL surgery from January 2010 to March 2015, with > 1 year of follow up were retrospectively analyzed. The surgical technique was based on individual surgeon preference. The best-corrected distance visual acuity (BCDVA), previous surgery, surgical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 24 publications
2
87
0
2
Order By: Relevance
“…; Medhivanan et al. ). Additionally, a single case of endophthalmitis, possibly related to scleral fixation and suture exposure, has been reported (Heilskov et al.…”
Section: Scleral‐fixated Iolmentioning
confidence: 98%
See 1 more Smart Citation
“…; Medhivanan et al. ). Additionally, a single case of endophthalmitis, possibly related to scleral fixation and suture exposure, has been reported (Heilskov et al.…”
Section: Scleral‐fixated Iolmentioning
confidence: 98%
“…Medhivanan et al. (), in a retrospective comparative analysis of retropupillary iris‐claw versus SIS IOL, reported significantly more cases of postoperative iritis, increased IOP and pupil ovalization in the iris‐claw group. Recently, a large prospective study of IOL exchange with retropupillary IC‐IOL versus PCIOL repositioning by scleral suture showed similar visual acuity results, however with a significantly higher incidence of iris injury in the IC‐IOL group (Kristianslund et al.…”
Section: Iris‐fixated Iolmentioning
confidence: 99%
“…Initially, iris-claw IOLs were implanted in the AC (prepupillary); however, posterior chamber (retropupillary) iris-claw IOL is gaining popularity because it is technically less challenging and has a shorter learning curve, when compared to the SF IOL. 6 In this implantation technique, the haptics of the poly methyl methacrylate (PMMA) IOL are anchored to the posterior surface of the iris, placing them far from the corneal endothelium and iridocorneal angle, which theoretically lowers the risk for endothelial and trabecular meshwork damage when compared to ACIOL. There is no general consensus about the best placement of iris-claw lens; however, a study reported that the AC implantation causes a higher endothelial cell loss (ECL) than the retropupillary one.…”
Section: Introductionmentioning
confidence: 99%
“…[101112] Recently, Madhivanan et al reported good outcomes using this technique compared to Gabor's technique of sutureless SFIOL placement over the long-term. [13] There are not many studies that directly compare outcomes of retropupillary iris claw IOL fixation with sutureless SFIOL techniques. Given the widespread use of Yamane's technique for SFIOL placement, it is imperative that we compare the outcomes of this technique with retropupillary iris claw IOL placement in the same setting.…”
mentioning
confidence: 99%